ANALISIS POTENSI BAHAYA MENGGUNAKAN METODE JOB SAFETY ANALYSIS (JSA) DAN JOB HAZARD ANALYSIS (JHA ) PADA PROSES NICKEL CHAIN DI PERTAMBANGAN NIKEL - SOFIA, SOFIA; BASUKI, MINTO (Nusantara of Engineering (NOE), 2025)
This research aims to identify potential dangers that exist in the mining process at PT. Putra Mekongga Sejahtera by using the JSA and JHA methods, mitigates potential dangers in the mining process. PT. Putra Mekongga Sejahtera by using the JSA and JHA methods, and implementing awareness of the importance of occupational safety and health at work sites using the JSA and JHA methods. This research uses two research methods, namely Job Safety Analysis and Job Hazard Analysis. The data collection method for JSA uses primary data and secondary data. Meanwhile, the instruments or data collection tools used in this research are interview guides and observation sheets based on the JHA form. So that the results of the interview can be recorded properly and researchers have evidence after conducting interviews with informants or data sources. The results of the research show that accidents that often occur in the mining process are on the hauling line (production line). All accidents occur on the hauling line. The highest cases occurred in June 2022 and resulted in lost work days in May 2023. Therefore, the application of Job Safety Analysis (JSA) and Job Hazard Analysis (JHA) is a tool to avoid work accidents. These potential hazards can be controlled by determining a priority scale first which can then help in prioritizing which can then help in selecting risk controls which is called the risk control hierarchy. The importance of implementing K3 awareness at work locations for company employees must be implemented and given special attention because this is a shared responsibility so support and support is really needed in the company, both from the leadership to the workers in the field.